Constructing the multilingual child: the case of language education policy in Norway. Issue 1 (1st January 2017) - Bubikova-Moan, Jarmila
ABSTRACT: The aim of this paper is to trace how the multilingual child has been variably constructed in Norway's language education policy discourse over time. This will be explored through an in-depth critical discourse analytical (CDA) reading of two official policy reports targeting specifically the situation of children of non-Norwegian ethnolinguistic heritage in Norway's educational system. The key analytical concept is intertextuality, connecting the various discursive layers of Norway's language education policy processes, each replete with a multitude of voices with a stake in shaping the language educational reality of Norway's young multilinguals. The paper demonstrates that there is a substantial intertextual differential in how the two reports draw on these voices to either challenge or endorse the structural forces of powerful institutions, such as the state, reflecting also the wider social and discursive current of change sweeping through the traditionally egalitarian welfare states of Northern Europe, such as Norway.